Henrietta Liston's travels : the Turkish journals, 1812-1820 - Liston, Henrietta, Lady, 1751-1828 (Edinburgh scholarship online., 2020)
Henrietta Liston's Turkish journal is a significant yet virtually unknown work of women's travel writing. As the wife of the British Ambassador to the Sublime Porte, Liston had privileged access to the Ottoman elite and diplomatic corps. Her journal reflects on British-Ottoman relations, combining Orientalist perspectives with a human-centred version of the picturesque. It offers astute commentaries on places, people and events -- including a plague-ridden Constantinople, a visit to the harem of the Grand Vizier's deputy, the presentation of ambassadors in the Seraglio and the departure of pilgrims on the hajj.--